Degree of the Image Body Satisfaction and Their Relation to Sport Trend of Pupils in Physical Education and Sports Lesson (Applied study in some Ouargla secondary-schools) - necir ahmida; جرمون علي; لماحي قصار (sports creativity, 2025)
The study aimed to estimating the degree of the image body satisfaction, and level of sporting trend, and The nature of the relationship between them to Secondary school pupils, the study sample consisted of (347) male pupils, They were randomly selected, the researchers used the descriptive approach, A scale was used body image and sporting trend scale. The results showed that the degree of the image body satisfaction and the level of sporting trend was height, and showed a positive statistically significant correlation between them among study sample